The day before - Schroeder, Lisa (Simon Pulse, 2011)
Sixteen-year-old Amber, hoping to spend one perfect day alone at the beach before her world is turned upside down, meets and feels a strong connection to Cade, who is looking for his own escape, for a very different reason.